2020
DOI: 10.1016/j.heliyon.2020.e04879
|View full text |Cite
|
Sign up to set email alerts
|

Gotong Royong as social capital to overcome micro and small enterprises' capital difficulties

Abstract: One of the micro and small enterprises' (MSEs) main problem is business capital. Cash flow shortage often interrupts business development. This difficulty is due to the limited ability in meeting the requirements to access sources of capital. The development of micro and small enterprises using the culture of the local community is a way to overcome this issue. Asians generally have the perception of Gotong Royong (which means 'mutual aid' in English) as a form of collectivism. This study comes from the gap wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 25 publications
(32 reference statements)
1
25
0
5
Order By: Relevance
“…The results of the accepted hypothesis testing support the results of previous studies that the attitude has a positive effect on intention, subjective norms have a significant effect on intention, perceived behavioural control has a positive effect on intention, and perceived behavioural control has a significant and positive effect on behaviour [15,35,37,40,42]. At the same time, there are no rejected hypotheses.…”
Section: Pls Methods Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…The results of the accepted hypothesis testing support the results of previous studies that the attitude has a positive effect on intention, subjective norms have a significant effect on intention, perceived behavioural control has a positive effect on intention, and perceived behavioural control has a significant and positive effect on behaviour [15,35,37,40,42]. At the same time, there are no rejected hypotheses.…”
Section: Pls Methods Analysissupporting
confidence: 84%
“…Subjective norms are social pressure on someone to do or not take action [34,35]. It has been observed that subjective norms positively and significantly affect energy consumption intention [36].…”
Section: Subjective Norm and Energy Efficiency Intentionmentioning
confidence: 99%
“…In traditional communities, gotong royong plays a vital role in the daily life of a community. The essence of gotong royong is that through mutual assistance, both individuals and the community benefit (Lukiyanto & Wijayaningtyas, 2020). Examples of gotong royong include collectively constructing homes and other forms of infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the definition from IEC/IEEE 42010:2011, Enterprise Architecture is considered as the science that manages organizational architecture, and the results are defined as follows: "Enterprise architecture is a fundamental science that manages the organization which is related to the components and the relationship between the environment and the principles in managing the design of the system." Some opinions about enterprise architecture: According to (Lukiyanto & Wijayaningtyas, 2020), "Enterprise is defined as an activity that has a purpose and provides mutual information with other resources". Enterprise Architecture (EA) is a strategy that companies carry out with very fast changes, following the rhythm of the market and gaining a global perspective (Gonçalves et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%